2017
DOI: 10.1016/j.ygyno.2017.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of circulating tumor cells (CTCs) captured by microfluidic device in patients with epithelial ovarian cancer

Abstract: Proof-of-concept was provided for an electrically conductive and nanoroughened microfluidic platform-based chip designed to capture CTCs in patients with EOC. A larger patient sampling and longer duration of follow-up are needed to determine its suitability for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 20 publications
(22 reference statements)
1
63
0
Order By: Relevance
“…The link between CTC clusters and resistance to treatments is becoming more and more obvious. Lee et al reported platinium resistance in primary or recurrent ovarian cancer associated with the presence of CTC clusters in peripheral blood [55]. Although not explained by the authors, the study highlights a correlation between CTC clusters and metastatic evolution.…”
Section: Towards Innovative Treatment Leveragementioning
confidence: 59%
“…The link between CTC clusters and resistance to treatments is becoming more and more obvious. Lee et al reported platinium resistance in primary or recurrent ovarian cancer associated with the presence of CTC clusters in peripheral blood [55]. Although not explained by the authors, the study highlights a correlation between CTC clusters and metastatic evolution.…”
Section: Towards Innovative Treatment Leveragementioning
confidence: 59%
“…While CTM detection at baseline generally indicated a lower PFS, persistence or appearance of CTM after therapy indicated reduced PFS highlighting the prognostic potential of CTM (Fanelli et al, 2017). Furthermore, it has been shown that in NSCLC patients CTM prevalence is correlated with stage of the disease whilst presence of CTM was correlated with resistance to therapy in epithelial ovarian cancer (EOC) patients (Lee et al, 2017). Taken together, these investigations suggest the potential for CTM as diagnostic, prognostic, and predictive biomarker.…”
Section: Ctm In Clinic: Diagnostic Prognostic and Predictive Potentialmentioning
confidence: 94%
“…Based on the precipitation of CTCs in the low-speed centrifuge, the leukocyte fractions can be distinguished via physical features as well. Lee et al used a nanoroughened microfluidic platform and detected CTCs in the sera of nearly all female participants (53/54, 98.1%) with ovarian cancer [12]. They also showed that although there is no relationship between CTC count and PFS in patients with newly diagnosed epithelial ovarian cancer (EOC), in patients with recurrent disease and chemoresistance; a relationship was found between CTC-cluster positivity and diminished OS [12].…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…Lee et al used a nanoroughened microfluidic platform and detected CTCs in the sera of nearly all female participants (53/54, 98.1%) with ovarian cancer [12]. They also showed that although there is no relationship between CTC count and PFS in patients with newly diagnosed epithelial ovarian cancer (EOC), in patients with recurrent disease and chemoresistance; a relationship was found between CTC-cluster positivity and diminished OS [12]. It has been postulated that CTCs could result in metastatic progression and recurrence by way of epithelial-mesenchymal-transition (EMT) or development of stem-like features and hence a reduced OS.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%